The Use of Authentic Tasks to Influence Fifth Semester Foreign Language Students’ Participation at a Colombian Public University (2019)
This research seeks to explore the influence of authentic tasks on fifth semester foreign language students’ participation at a public university in the Caribbean coast of Colombia. Through the examination of EFL learners' participation in the natural setting, this study aims at designing, implementing, and assessing the use of authentic tasks for the improvement of students’ participation in English classes. This study is based on a qualitative research approach which allows to study and observe a problem in its natural setting (Denzin & Lincoln, 2013). It uses an action-case study which intend to solve a problem and to improve it for students’ learning process. Data will be gathered through classroom observations, video recordings, rubrics and questionnaires. The results aimed at contributing to influence fifth semester foreign languages students’ participation through the use of authentic tasks.